Effect of Preactivation on Torque Enhancement by the Stretch-Shortening Cycle in Knee Extensors - Fukutani, Atsuki (PLoS One, 2016)
The stretch-shortening cycle is one of the most interesting topics in the field of sport sciences, because the performance of human movement is enhanced by the stretch-shortening cycle (eccentric contraction). The purpose of the present study was to examine whether the influence of preactivation on the torque enhancement by stretch-shortening cycle in knee extensors. Twelve men participated in this study. The following three conditions were conducted for knee extensors: (1) concentric contraction without preactivation (CON), (2) concentric contraction with eccentric preactivation (ECC), and (3) concentric contraction with isometric preactivation (ISO). Muscle contractions were evoked by electrical stimulation to discard the influence of neural activity. The range of motion of the knee joint was set from 80 to 140 degrees (full extension = 180 degrees). Angular velocities of the concentric and eccentric contractions were set at 180 and 90 degrees/s, respectively. In the concentric contraction phase, joint torques were recorded at 85, 95, and 105 degrees, and they were compared among the three conditions. In the early phase (85 degrees) of concentric contraction, the joint torque was larger in the ECC and ISO conditions than in the CON condition. However, these clear differences disappeared in the later phase (105 degrees) of concentric contraction. The results showed that joint torque was clearly different among the three conditions in the early phase whereas this difference disappeared in the later phase. Thus, preactivation, which is prominent in the early phase of contractions, plays an important role in torque enhancement by the stretch-shortening cycle in knee extensors.